Implementasi Stretching Exercise Untuk Mengurangi Nyeri Sendi Extremitas Bawah Pada Lansia Dengan Gout Arthritis (GA) Di UPTD Lanjut Usia Binjai - Josia Edyanta Purba; Mucti Yuda Pratama; Nina Olivia (STIKES Columbia Asia Medan, 2025)
Gout arthritis is a metabolic disease characterized by elevated uric acid levels in the blood. This condition causes joint pain, especially in the lower extremities. Elderly people with gout arthritis often experience decreased mobility and quality of life due to chronic joint pain. Stretching exercises are an effective non-pharmacological intervention to reduce pain and increase joint flexibility. The purpose of this study was to examine the implementation of stretching exercises in reducing lower extremity joint pain in elderly people with gout arthritis. This study used a descriptive case study approach that applied the medical-surgical nursing care process, including assessment, diagnosis, intervention, implementation, and evaluation. This study used two elderly subjects with gout arthritis and moderate pain scales. Stretching exercises were implemented twice daily for 25-30 minutes for six days, based on the development of nursing interventions according to SIKI (2018). The results showed a decrease in moderate pain scale to mild pain scale after the implementation of stretching exercises in both subjects for six days. The results of this study are expected to be implemented independently and provide motivation to improve the quality of life of gout arthritis sufferers.